Теоретичні підходи до визначення конкурентних позицій підприємства на ринку - Соколова, Л. В.; Гінда, Ю. О. (ХНУРЕ, 2018)
The theoretical approaches to the definition of competitive positions of the enterprise in the market are considered. The definition of the concept of a competitive position of the enterprise is given. The stages of research of competitive positions of industrial enterprises are generalized.
Keywords: конкурентне середовище; конкурентні позиції